Shock, Trauma, and Polarization: Finding Unity in a World of Dualities - Maley, Michael (Bioenergetic Analysis, 2022)
Polarization and disconnection represent the most difficult and harmful threat to our life force and vitality and are often at the core of our client’s symptoms. This paper discusses two of the most polarized emotional states we encounter in our clinical work – shame and trauma – and some ways to view the healing of those states.